Applications of Vertebrate Models in Studying Prostatitis and Inflammation-Associated Prostatic Diseases - Bleeker, Joosje; Wang, Zhu A. (Frontiers in Molecular Biosciences, 2022)
It has long been postulated that the inflammatory environment favors cell proliferation, and is conducive to diseases such as cancer. In the prostate gland, clinical data implicate important roles of prostatitis in the progression of both benign prostatic hyperplasia (BPH) and prostate cancer (PCa). However, their causal relationships have not been firmly established yet due to unresolved molecular and cellular mechanisms. By accurately mimicking human disease, vertebrate animals provide essential in vivo models to address this question. Here, we review the vertebrate prostatitis models that have been developed and discuss how they may reveal possible mechanisms by which prostate inflammation promotes BPH and PCa. Recent studies, particularly those involving genetically engineered mouse models (GEMMs), suggest that such mechanisms are multifaceted, which include epithelium barrier disruption, DNA damage and cell proliferation induced by paracrine signals, and expansion of potential cells of origin for cancer. Future research using rodent prostatitis models should aim to distinguish the etiologies of BPH and PCa, and facilitate the development of novel clinical approaches for prostatic disease prevention.